2012
DOI: 10.1073/pnas.1215037109
|View full text |Cite
|
Sign up to set email alerts
|

Slime mold uses an externalized spatial “memory” to navigate in complex environments

Abstract: Spatial memory enhances an organism's navigational ability. Memory typically resides within the brain, but what if an organism has no brain? We show that the brainless slime mold Physarum polycephalum constructs a form of spatial memory by avoiding areas it has previously explored. This mechanism allows the slime mold to solve the U-shaped trap problem-a classic test of autonomous navigational ability commonly used in robotics-requiring the slime mold to reach a chemoattractive goal behind a U-shaped barrier. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
175
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 35 publications
2
175
1
Order By: Relevance
“…Many microorganisms possess complex communication mechanisms that allow them to interact with one another [35]; now we can add the true slime moulds to the list. In a precedent study, we showed that cells leave an extracellular slime while exploring their environment, and use it to avoid areas previously explored and navigate in a complex environment [17]. Here we show that cells while feeding also leave chemicals in the environment, which are attractive to congeners.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Many microorganisms possess complex communication mechanisms that allow them to interact with one another [35]; now we can add the true slime moulds to the list. In a precedent study, we showed that cells leave an extracellular slime while exploring their environment, and use it to avoid areas previously explored and navigate in a complex environment [17]. Here we show that cells while feeding also leave chemicals in the environment, which are attractive to congeners.…”
Section: Discussionmentioning
confidence: 91%
“…It crawls around forming extended pseudopods in order to search for food. Slime moulds have been known for decades for their amazing abilities such as finding their way in a maze [15], solving nutritional challenge [16], avoiding traps [17] and anticipating periodic events [18]. These are just a few examples of our growing understanding of these unusual organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell forms pseudopods and creeps along various surfaces at a maximum speed of 4 cm per hour. P. polycephalum demonstrates amazing abilities, such as finding its way through a maze [13], building a smart network [14], solving complex nutritional challenges [15], avoiding being trapped [16] and anticipating periodic events [17]. In addition, P. polycephalum exhibits a form of self-signalling and shows chemoattractive movements towards other individuals [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our work builds on the growing body of evidence suggesting that slime moulds are capable of making complex decisions that integrate information from a variety of sources (Latty and Beekman, 2009, 2011aDussutour et al, 2010;Reid et al, 2012. Here, we show that, despite being little more than giant amoebae, slime moulds use departure heuristics similar to those used by many animals, including humans.…”
Section: Discussionmentioning
confidence: 98%